Low rural health insurance take‐up in a universal coverage system: perceptions of health insurance among the uninsured in La Guajira, Colombia. (1st September 2013) - Buttorff, Christine; Trujillo, Antonio J.; Ruiz, Fernando; Amaya, Jeannette L.
Summary Despite enacting a universal healthcare system in 1993, many Colombians do not participate. Understanding perceptions of the system could help the government market certain features or adjust benefits in order to increase enrollment. Using La Guajira, Colombia, as a case study, we surveyed uninsured rural households regarding insurance preferences, values and beliefs, and perceptions of available services. Four hundred heads of households responded in La Guajira, Colombia. Respondents reported high levels of long‐term uninsurance. Overall, the quality of services in the government‐run system is perceived as better than being uninsured, but there appear to be constraints on enrollment. Rural Colombians value more family coverage and better choice of physicians, but offering better benefits may not be enough. Many cited access barriers, so reducing these barriers may also increase enrollment. Further surveys in other parts of Colombia should be undertaken to confirm results. Copyright © 2013 John Wiley & Sons, Ltd.